Servitization strategy and managerial control - Pistoni, Anna,; Songini, Lucrezia, (Studies in managerial and financial accounting ;)
Manufacturing firms are moving beyond manufacturing to offer services and solutions, often delivered through their products, or at least in association with them. This strategy is called “servitization” and these new business models are based on the Product-Service-System (PSS). This book, through both a theoretical and an empirical approach, intends to present and discuss the main challenges that companies interested in servitization strategies have to overcome, with a particular focus on the design of managerial control systems. This book can represent a useful tool for whose companies interested in the development of successful servitization strategies and for scholars involved in research on innovative business models. In particular, it may be of interest for top management and middle management in charge of strategic and organizational issues, as well organizational units, such as: supply chain, logistics, production, after sales and service, R&D, strategic planning and managerial control. Consultants and practitioners involved in strategy, organization, manufacturing, operations, supply chain and managerial control may be interested too.